Energy Regulation, Roll Call Votes and Regional Resources: Evidence from Russia - Theocharis N. Grigoriadis; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2006)
This paper investigates the relative impact of regional energy production on the legislative choices of Russian Duma deputies on energy regulation between 1994 and 2003. We apply Poole's optimal classification method of roll call votes using an ordered probit model to explain energy law reform in the first decade of Russia's democratic transition. Our goal is to analyze the relative importance of home energy on deputies' behavior, controlling for other factors such as party affiliation, electoral mandate, committee membership and socio-demographic parameters. We observe that energy resource factors have a considerable effect on deputies' voting behavior. On the other hand, we concurrently find that regional economic preferences are constrained by the public policy priorities of the federal center that continue to set the tone in energy law reform in post-Soviet Russia.
Keywords: Q40; D72; K23; P27; P37; P31; R11; 330; energy regulation; energy roll law reform; energy resources; roll call votes; legislative politics; State Duma; Russia